Healthy lifestyle behaviors among university students in Ukraine (Environment & Health, 2017)
Aim. The study aims to assess adherence of Ukrainian university students to healthy lifestyle behaviors.Materials and Methods.The survey among volunteer students (n=211, 49.3% of females) of two universities of Kyiv region, central part of Ukraine was carried out. Odds ratio approach was used for statistical analysis.Results. Among Ukrainian university students aged 17-21, only 7.1% were overweight. And significant part of students (74.8% of males and 56.7% of females) reported sufficient level of daily physical activity. On the other hand, 25.6% of students smoked and 61.6% consumed alcohol (at least rare). Less than half of students consumed sufficient amount of fruits and vegetables, and milk and dairy products daily. Over 70% of students admitted negative effects of the environment on their health and recognized their insufficient economic status for better adherence to healthy lifestyle.Conclusions. Ukrainian student youth demonstrate better adherence to healthy lifestyle as compared to older generations, but smoking and alcohol consumption are still the significant threats to young people health.
Keywords: health; lifestyle; youth; environment; smoking; alcohol; diet; physical activity